Assessment of heat transfer behavior of water based alumina nanofluid. (2018) - Balaji, V.; Arulprakasajothi, M.; Logesh, K.; Tharunpillai, B.
Abstract: Experimental investigations were performed on the heat transfer characteristics of Al2O3 -H2 O nanofluids using KD2 Pro thermal analyzer. Different volume fractions with concentrations of 0.5% and 0.75% were employed. The boost in the thermal conductivities was observed to be 9.44 and 13.22 for volume concentrations of 0.5% and 0.75% respectively. The results show that the thermal conductivity enhancement coincides with the Maxwell and Choi model. We were also able to assimilate our results to similar studies and illustrate it to have satisfactory coincidence. The viscosities of Al2 O3 /H2 O Nanofluids were measured for different particle concentrations using Brookfield Dial Viscometer. The viscosity values showed a rise with nanoparticle concentration.